Nanometer-scale field-induced oxidation if Si(111): H by a conducting-probe scanning force microscope: Doping dependence and kinetics - Hundhausen, Martin; Ley, Lothar; et al. (Applied Physics Letters, 1995)
Hydrogen-terminated Si(111) was patterned on the nanometer scale by field-induced oxidation using a biased conducting-probe scanning force microscope. The kinetics of oxide growth as well as its dependence on doping are investigated. Field-induced oxidation is observed for voltages exceeding a doping dependent threshold above which oxidation kinetics follows a power law.© 1995 American Institute of Physics.
UnivIS-Import:2015-04-14:Pub.1995.nat.dphy.IAP.exphys.nanome_5